(untitled) (Al-Academy, 2019)
The present study aimed at ((building an educational -learning design based on the theory of Merrill in (CDT) and measuring the effectiveness of this design in the motivation and achievement of the high school fifth grade students to art education in the subject of the history of modern art)). The research community is made of fifth grade preparatory students in the secondary school of Umm Ayman in the Directorate of Education of Baghdad / Ar-Rusafa in a simple random way. The study sample (58 students) was chosen from section (e) to study according to Merrill theory (CDT) and section (d) to study according to the traditional way. The pilot design of the control and experimental equivalent groups that have partial control in the post-test was selected. Teaching plans according to Merrill theory (CDT) and teaching plans in the traditional way were prepared. In addition, multiple choice achievement tests and a learning motivation scale were prepared for this purpose. The researcher used a number of statistical methods suitable for this study.The results showed that the experimental group, which was taught according to the Merrill theory (CDT), was superior in learning and achievement motivation to the control group which was taught in the traditional way. The researcher, in light of the results, made a number of recommendations and suggestions for this study